Sustainability Reporting And Accounting By The Indian Corporates (Journal of Pharmaceutical Negative Results, 2023)
Industry 5.0 is the 5th industrial revolution in which people will be working along with smart technology and robots. Technological advancement will help humans to work better and more productively by leveraging IoT, AI, and big data. It also helps us in enhancing the efficiency and effectiveness of the performance of the corporate world and simultaneously the economy as a whole by adapting technology-based tools such as IoT, real-time data, analytics, AI, and cloud computing. In the 21st century, the challenge of sustainable development is an imperative problem in front of every corporate entity. It is a need of the hour to have a strong bonding between corporate success and the sustainability aspects of companies.  Now a day, sustainability reporting and accounting by companies are a gaining lot of importance over the past decades. Global Reporting Initiative has made substantial developments in reporting formats by disclosing important information and reports by the companies. The significance of sustainability accounting and reporting has been underlined by Government entities, Non-Government entities, and NGOs.Sustainability reporting and accounting are gaining momentum as important communication tools for corporate entities to disclose their sustainability plans and performance and enhance stakeholders’ confidence.This chapter discussed how excellence is attained by corporates or firms through the proposed sustainability reporting and accounting models or frameworks with the help of their strategic vision, mission, and goals.